Efektivitas Model Pembelajaran Group Investigation dalam Meningkatkan Hasil Belajar IPA Terpadu Siswa SMP - Yusniar Gulo (Program Studi Pendidikan Biologi - Universitas Nias, 2024)
Low learning outcomes in integrated science among junior high school students remain a major issue, largely influenced by the dominance of conventional teaching methods and the limited active engagement of students in the learning process. This study aimed to analyze the effectiveness of the Group Investigation learning model in improving integrated science learning outcomes. A quasi-experimental design with a non-equivalent control group was employed, involving 42 seventh-grade students divided into an experimental group and a control group. Data were collected using essay-based learning achievement tests administered before and after the treatment. Data analysis was conducted using both descriptive and inferential statistics, including a two-tailed t-test after fulfilling normality and homogeneity assumptions. The results indicated that the average learning outcomes of the experimental group were higher than those of the control group, with a more significant improvement observed. Hypothesis testing revealed a statistically significant difference between the two groups at the 5% significance level. These findings suggest that the Group Investigation model is effective in enhancing integrated science learning outcomes through active student engagement and collaborative learning processes.